Penguatan Sikap Teladan R.A. Kartini terhadap Mahasiswa Berdasar pada Hasil Desiminasi Bincang Inspiratif Wanita Hebat Mathla’ul Anwar - Saraswati Saraswati; Purlilaiceu Purlilaiceu; Ika Meika; Ari Fajria Novari; Fadhila Malasari Ardini; Trisnawati Trisnawati; Ika Yunitasari; Nur Azmi Rohimajaya; Nenden Suciyati Sartika (Universitas Mathla'ul Anwar Banten, 2021)
STRENGTHENING THE EXAMPLE OF R.A. KARTINI TOWARDS STUDENTS BASED ON THE RESULTS OF THE DISSEMINATION OF GREAT WOMEN INSPIRATIONAL TALKS MATHLA'UL ANWAR. This community service activity aims to provide empowerment to Mathla'ul Anwar University students based on the results of the dissemination of the Mathla'ul Anwar Inspirational Talk activity for Great Women. This activity was held to coincide on April 21, 2021 with the target of students residing in the Mathla'ul Anwar University environment from various majors or study programs. The holding of the Mathla'ul Anwar Inspirational Talk event was a form of appreciation for the role and struggle of Raden Ajeng Kartini in advancing the nation, especially for women whose roles were still limited at that time. By raising the theme of strengthening R.A Kartini's exemplary attitude, it is hoped that R.A Kartini's exemplary attitudes and traits can be transmitted to Indonesian women, especially women in Mathla'ul Anwar University. Through his fighting spirit and attitude, the figure of R.A Kartini can be an inspiration and able to awaken the younger generation to join the spirit and become a creative person.